Effects of Goose Collagen and Collagen Peptide on Osteoporosis. Issue 10 (2nd October 2016) - Wang, Pingping; Jiang, Jinli; Pan, Daodong; Sun, Yangying; Wu, Zhen; Cao, Jinxuan; Zeng, Xiaoqun
Abstract : The effects of collagen and collagen peptide from goose bone on osteoporosis were studied. Fourier transform infrared spectrometry, ultraviolet spectrum, differential scanning calorimetry, and sodium dodecyl sulfate polyacrylamide gel electrophoresis identified the goose collagen as typical type I collagen. Results showed that osteopontin, bone morphogenetic protein 2, runt-related transcription factor 2, and type I collagen levels in bone marrow mesenchymal stem cells supernatant were dramatically higher in the experimental groups than in the control group ( p < 0.05), and was highest in the experimental group composed of low molecular weight collagen peptide linked with calcium. Then the osterix, runt-related transcription factor 2, transforming growth factor-β1, and bone morphogenetic protein 2 expression levels related to osteogenetic differentiation were detected by real-time fluorescent quantitative polymerase chain reaction. The findings showed that goose collagen and collagen peptide can improve the gene expression related to osteogenetic differentiation which reflected the level of bone marrow mesenchymal stem cells to osteoblasts.